Russia-Ukraine War: Geopolitical Implications and Evolution of NATO-Russia Relations - Zhao, Yingshu (Université d'Ottawa | University of Ottawa, 2023)
This study examines how the conflict between Russia and Ukraine has affected international politics, focusing on how cooperation between Russia and NATO has broken down. Therefore, the research approach is a qualitative systematic literature review, and it examines scholarly papers, foreign policy reports, and websites like Carnegie Europe and the Atlantic Council that deal with international relations. Simultaneously, Russia's annexation of Crimea in 2014 and the subsequent escalation of the conflict into a full-scale war in 2022 have had far-reaching consequences for international peace and safety and political and economic stability. In addition, significant shifts in Russia-NATO ties, repercussions for Ukraine's future NATO membership, and security concerns for neighbouring nations like Finland and Sweden are all highlighted in the study. Subsequently, the research also examines how the conflict has affected the Ukrainian economy, focusing on the country's reliance on imported energy and the urgent need for economic restoration. The study also sheds insight into how the war and the large-scale emigration of Russian nationals seeking better economic prospects have affected the country's demographic makeup. As a concluding remark, significant geopolitical ramifications coming from the Russia-Ukraine conflict are discussed in this study. Likewise, Ukraine's hopes of joining NATO have been damaged, while neighbouring nations like Finland and Sweden have sought stronger connections with NATO for increased security in response to the crisis. Similarly, the emergence of new, pressing challenges, such as energy dependence and economic rehabilitation in Ukraine and demographic shifts in Russia as a result of military service and migration, highlighted the war's far-reaching impacts. As a result, insightful information on the changing dynamics of the area and the difficulties of post-conflict international cooperation and security is gleaned from the comprehensive literature research.